Can EPTS be used for measuring sprinting times in Ice Hockey? - Link, D.; Weber, M. (Sportinformatik XII. 12. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie" vom 5.-7. September 2018 in Garching. Abstracts., 2018)
The acquisition of sprint times with regard to the athlete`s progress in this discipline is an important parameter in many sports. A precise evaluation of this performance requires expensive hardware such as a gun coupled high-speed camera and comes with the downside of only being useful in this particular setting, whilst not being available during competition. ln recent years, electronic performance and tracking systems (EPTS) have emerged as a universally applicable alternative. The precision of different EPTS has been evaluated for outdoor sports in many instances, yet to date no validation has been provided for ice hockey. Due to movement on ice being different in nature, there is reason to believe that the manufacturers` filter algorithms for positional data need to be adjusted for this type of sports. Therefore, the aim of this study is to evaluate the precision of measuring sprinting times of three different EPTS in standardised settings. The results should prove useful in estimating the limits, to which these systems are capable of registering minimal performance changes in different movement conditions.